Filming and Performing Renaissance History
XIII, 212 p.
Keywords: Over the last century, many 16th- and 17th-century events and personalities have been brought before home, cinema, exhibition, festival and theatrical audiences. This collection examines these representations, looking at recent television series, documentaries, pageantry, theatre and popular culture in various cultural and linguistic guises.